The Strategic Role of Islamic Education Management in Integrating Islamic Value-Based Character Education in the Digital and Technology Era - Aulia, Afifah; Yuliyanti, Yuliyanti (IJoIS: Indonesian Journal of Islamic Studies, 2024)
This research discusses the role of Islamic education management in integrating Islamic value-based character education in the digital era. Islamic character education, which focuses on moral and ethical formation, is important as a value foundation in the midst of rapid technological development. Islamic education management plays a strategic role in designing an Islamic character-based curriculum, developing Islamic digital learning media, and empowering teachers as role models for students. Through the use of technology and social media, Islamic values can be more easily accessed and accepted by the younger generation, forming a strong character that is in accordance with Islamic principles. This research uses a qualitative method with a descriptive-analytical approach, which is carried out through literature studies and content analysis of various related academic sources. The results show that Islamic education management can optimize the role of technology in supporting Islamic character education, including the implementation of a curriculum based on Islamic values, relevant digital learning media, and active participation from parents and the community in supporting the formation of students' Islamic character. In conclusion, the strategies implemented by Islamic education management have the potential to form a generation that excels academically and has Islamic character, ready to face the challenges of the digital era with the basis of faith and noble character.